Funcionarios de la Oficina de Transportes. (UNED, 2024)
Aparecen de izquierda a derecha William Villalobos Chavarría-Jefe de Transportes, Carlos Luis Retana Romero, Manuel Antonio Porras Vargas, José Luis Robles Thames, Víctor Hugo Barquero Alfaro, agachados de izquierda a derecha de primero Rodrigo Mora Soto, José Joaquín Solano Zeledón, Jorge Arguedas Rodríguez y Gerardo Cordoba Brenes